2018
DOI: 10.1186/s40959-018-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of cancer treatment-related cardiomyopathy among referrals for advanced heart failure

Abstract: Background: Approximately 2-3% of patients undergoing advanced heart failure therapies such as left ventricular assist devices (LVAD) and orthotropic heart transplantation (OHT) have chemotherapy-related cardiomyopathy, according to analyses of large databases such as United Network for Organ Sharing (UNOS) or Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) registries. While these studies have shown similar survival outcomes post-interventions, these databases by definition exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
1
15
0
2
Order By: Relevance
“…Araujo-Gutierrez et al (145) analyzed all the referrals for advanced HF of a tertiary-care center, showing that 3.4% of patients were CCMP, but the percentage was high as 7.8% in the subset of idiopathic, non-ischemic cardiomyopathy. Though not reaching statistical significance, there was a higher percentage of patients receiving LV assist device (LVAD) as bridge to transplant (BTT).…”
Section: Acute-on-chronic Heart Failure and Advanced Heart Failure Therapies For Chemotherapy-induced Cardiomyopathy Patientsmentioning
confidence: 99%
“…Araujo-Gutierrez et al (145) analyzed all the referrals for advanced HF of a tertiary-care center, showing that 3.4% of patients were CCMP, but the percentage was high as 7.8% in the subset of idiopathic, non-ischemic cardiomyopathy. Though not reaching statistical significance, there was a higher percentage of patients receiving LV assist device (LVAD) as bridge to transplant (BTT).…”
Section: Acute-on-chronic Heart Failure and Advanced Heart Failure Therapies For Chemotherapy-induced Cardiomyopathy Patientsmentioning
confidence: 99%
“…These differences result from the presence of women specific forms of primary disease and sex-specific biological response. The most common forms of CRCD are secondary to breast cancer treatment, which is strongly sexoriented, followed by hematological malignancies [22,51]. Women with CRCD that progressed to DCM are older, have smaller end-diastolic volume index, have higher left ventricular EF, have a lower burden of scar at CMR, have a worse NYHA class but a better long-term prognosis, and have higher rate of previous chemotherapy exposure compared with women with the diagnosis of primary DCM [52][53][54].…”
Section: Sex-related Differences In Chemotherapy-related Cardiac Dysfmentioning
confidence: 99%
“…In this setting, DCM can be the ending phase of a pathological process that is usually defined more broadly as chemotherapy-related cardiac dysfunction (CRCD). It is reported that CRCD can affect up to 10% of cancer survivors [22], even though incidence is variable according to the definition used. The heterogeneity of definitions adopted by different societies is summarized in Table 1 [23,24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular diseases and cancer are the most common death causes in the USA and Europe, although long-term survival of oncological patients has increased in the last years, reaching 64% of 5-year survival rate, 41% of 10-year survival rate and 15% of 20-year survival rate. Moreover, many patients suffer from both of these conditions – a situation which may result from cardiotoxicity of anticancer treatment 1,2. The most frequent symptom of such cardiotoxicity is LVEF (left ventricular ejection fraction) reduction which may indicate the development of left ventricular dysfunction and lead to congestive heart failure.…”
Section: Introductionmentioning
confidence: 99%